Carvacrol, a Plant Metabolite Targeting Viral Protease (Mpro) and ACE2 in Host Cells Can Be a Possible Candidate for COVID-19 - Javed, Hayate; Meeran, Mohamed Fizur Nagoor; Jha, Niraj Kumar; Ojha, Shreesh (Frontiers in Plant Science, 2021)
The recent outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) started in December 2019, resulting in the coronavirus disease-19 (COVID-19) pandemic. Coronaviruses are solely accountable for rising mortality and socioeconomic saddles. Presently, there are few repurposed drugs such as remdesivir or favipiravir approved for the treatment of COVID-19, although vaccines and plasma therapy is also subject to emergency approval. However, some potential natural treatments and cures have also been proposed. Molecules of natural origin showed therapeutic importance such as antiviral, anti-inflammatory, and antioxidant activity, and could be useful drug candidates for treating COVID-19. In recent years, essential oils have shown promising therapeutic effects against many viral diseases. Carvacrol is one of the monoterpene phenol with abundant presence in essential oils of many aromatic plants, including thyme and oregano. It is being used as food flavoring, additive, and preservatives. Carvacrol is also used as a fragrance in cosmetic products. A number of research studies have shown biological actions of carvacrol with its therapeutic potential is of clinical significance. The in vitro and in vivo studies have shown multiple pharmacological properties such as anticancer, anti-fungal, anti-bacterial, anti-oxidant, anti-inflammatory, vasorelaxant, hepatoprotective, and spasmolytic. This review highlights the various biological and pharmacological properties of carvacrol within the scope of COVID-19.